MEDIA COOPERATION AS A PLATFORM TO IMPLEMENT SCIENTIFIC AND EDUCATIONAL PROJECTS AND TO FORM THE TERRITORY IMAGE - Georgiy V. Korshunov; Daniil O. Yur’Ev; Viktoriya A. Pul’Kina (Высшее образование в России, 2016)
The international informational project of branch media-cooperation between higher education institutions and the enterprises of fuel and energy complex is described in the article. Also the role of similar projects for realizationofeducational programs, introduction of new forms of cooperation and development of territories by means of imagemaking is analyzed. The project «UTimenews» is accomplished within the framework of innovation and technology consortium uniting the universities and companies of mineral sources and fuel and energy complex.